Financial Awareness Among the Teachers - Abdul Holik; Sri Mulyeni (Economics Development Analysis Journal, 2019)
People are vulnerable into economic difficulties if they do not have financial awareness. This study seeks to find out what the determinants of financial intelligence in junior and vocational school teachers in an area of West Java are. Our findings explain, in general, that teachers have relatively high financial awareness. Empirical tests suggest the financial awareness is influenced by an only one independent variable, namely a person's attitude. While the other independent variables such as family and individual perceptions are not significant at all. This finding proves the need for character education for everyone to have financial awareness. The reason is, the more mature a person, then the most determines everything in the life is his/ or her attitude, not anything coming from the family or something perceived so far.